2008
DOI: 10.1007/s11999-008-0283-7
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotectant and Radiosensitizer Effects on Sterility of γ-irradiated Bone

Abstract: Gamma radiation is widely used to sterilize bone allografts but may impair their strength. While radioprotectant use may reduce radiation damage they may compromise sterility by protecting pathogens. We assessed the radioprotective potential of various agents (L-cysteine, N-acetyl-L-cysteine, L-cysteine-ethyl-ester and L-cysteinemethyl-ester) to identify those which do not protect spores of Bacillus subtilis. We hypothesized charge of these agents will affect their ability to radioprotect spores. We also deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Methods to reduce the effect of irradiation or recover allograft strength therefore remain important to pursue. Irradiated bone allograft can be subjected to free radical scavenger treatment or crosslinking agents to restore some of the strength of the collagen backbone after testing [3,39,58,61,62]. Our study provides an S-N relationship at standard radiation dose, which can be useful in future studies that seek to maintain allograft strength after sterilization.…”
Section: Discussionmentioning
confidence: 97%
“…Methods to reduce the effect of irradiation or recover allograft strength therefore remain important to pursue. Irradiated bone allograft can be subjected to free radical scavenger treatment or crosslinking agents to restore some of the strength of the collagen backbone after testing [3,39,58,61,62]. Our study provides an S-N relationship at standard radiation dose, which can be useful in future studies that seek to maintain allograft strength after sterilization.…”
Section: Discussionmentioning
confidence: 97%
“…Ribose was chosen because: (a) it can diffuse into the bone (o300 Da) (Kattaya et al, 2008;Tami et al, 2003), (b) it crosslinks bone collagen (Vashishth et al, 2001;Willett et al, 2013), (c) crosslinking is oxidation dependent (Fu et al, 1992), d) ribose polymerizes when exposed to γ-irradiation (Bailey et al, 1961) and e) good cytocompatibility of ribose cross-linked collagen matrices has been reported (Brodsky et al, 1990;Girton et al, 1999;Roy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended to use a molecule with molecular weight smaller than 300 Da in order to increase the diffusion in cortical bone matrix (Akkus et al, 2005;Shuster, 2005). An investigation of the radioprotectant and radiosensitizer effects on sterility of gamma irradiated bones showed that the LC did not have radioprotective effect on spores of Bacillus subtilis irradiated in the range of 0.64 Mrad (Kattaya et al, 2008). Furthermore, it has been reported that the negatively and neutral charged scavengers are repelled from the capsule by the repulsion of charges, and therefore those scavengers do not enter the intracellular space and do not protect the bacteria (Shuster, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Shuster (2005) suggested that the proper scavenger should allow for the protection of the collagen structure of the allograft tissue but not the pathogens during irradiation. In another study, Kattaya et al (2008) investigated some cysteine-derived radioprotectants which can efficiently perfuse bone yet minimally protect pathogens. They showed that LC radioprotectant does not shield bacterial spores against gamma radiation and may be suitable for curbing the radiation damage to bone grafts while achieving sterility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation